The economic functions of gold - Shannon, Ian. (Melbourne : Cheshire, 1962)
This book examines the problems inherent in international monetary history and practice. It put forward a compromise solution that ensure understanding and co-operation in the international monetary system.
Includes index
Bibliographic footnotes.
usc 07/09/2017
Loans
Keywords: Gold; Gold standard; Currency question